A Systematic Review Comparing Different Security Measures Adopted in Automated Teller Machine - et.al, Anjalin Joy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The automated teller machines (ATM) uses are increasing day by day. Majority of the population uses ATM cards for shopping and cash withdrawal from ATMs. Along with increasing use of ATM cards the numbers of ATM thefts are also increasing worldwide. Majority of the ATM thefts are by manipulating or cloning the card. The incidences of physical ATM attacks by breaking into the ATM are also increasing worldwide. The securities of the customers are important in ATM transactions. The customers are protected from both physical and fraudulent ATM attacks by enhanced security measures provided by the bank. Majority of the ATMs provide fraud attacks by using a valid ATM card and PIN which could be easily identified and manipulated resulting in thefts. This paper discusses about the enhanced security measures implemented like face recognition, fingerprint identification, sensors to detects physical attacks along with PIN in various literatures. The merits and demerits of each security systems are compared.